2021
DOI: 10.7759/cureus.17252
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Outbreak on Orthopedic Surgery: A Nationwide Analysis of the First Pandemic Year

Abstract: To analyze the impact of the coronavirus disease 2019 (COVID-19) outbreak during the first pandemic year in a single country. MethodsA cross-sectional study was designed. The free access database of the Chilean Department of Statistics and Health Information (DEIS) was used to compare the number of orthopedic procedures between 2019 and 2020. Country mobility was exported from the Institute of Complex Engineering Systems (ISCI) free-access database; this corresponds to a direct measurement of the degree of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
(41 reference statements)
0
14
0
1
Order By: Relevance
“…Two studies [ 33 , 40 ] reported the impact on orthopedic performance in America ( Table 6 ). A study in the United States included 2830 cases for multi-subspecialty percentages analysis (pre-COVID-19 vs. post-COVID-19: 1917 vs. 913).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies [ 33 , 40 ] reported the impact on orthopedic performance in America ( Table 6 ). A study in the United States included 2830 cases for multi-subspecialty percentages analysis (pre-COVID-19 vs. post-COVID-19: 1917 vs. 913).…”
Section: Resultsmentioning
confidence: 99%
“…All types of surgical performance were affected, with knee arthroplasty having the greatest impact (−64%), followed by knee ligament reconstruction (−44%) and hip replacement (−41%). Trauma surgery/fracture was least affected [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the data may not be available from some countries. The reduction percentage of the volume of all surgeries was 49.4% in Germany [14], 44.2% in Hong Kong [30], 35% in Taiwan [55], 33% and 26% in the United Kingdom [19,21], 22.8% in Chile [32], and 15.6% in Australia (Figure 1, [49]). Surprisingly, even though there were few COVID-19 cases in the first wave and no serious lockdowns or restrictions in Hong Kong and Taiwan, they still experienced a substantial impact on the number of surgeries.…”
Section: Comparable Reduction Percentage Of All Surgeries and Electiv...mentioning
confidence: 96%
“…Knee replacement (−64%) had the greatest adverse impact, followed by hip replacement (−41%) and knee ligament reconstruction (−44%). The number of orthopedic surgeries was slightly correlated with the number of COVID-19 cases per month (p = 0.08) and strongly correlated with the country's mobility (p = 0.0001) [32].…”
Section: North and South Americamentioning
confidence: 96%
See 1 more Smart Citation